Filmmaking business processes for video content production in modern social media (Herald of Journalism, 2024)
The article emphasizes the significance of visual storytelling and the challenges that filmmakers encounter while promoting their work on social media platforms. This study seeks to evaluate marketing techniques for showcasing media content on social platforms and to identify effective strategies for leveraging platform algorithms. The theoretical section outlines essential phases of media content creation, spanning from script writing to post-production, highlighting the equal importance of creative vision and technical skill.  Additionally, the article addresses the global issues affecting media in Kazakhstan. The research methodology encompasses an analysis of social media algorithms as well as an experimental case study aimed at exploring their effects on video production practices. The article thus provides an example and discusses the contribution of social networks such as YouTube and TikTok to global content development. For example, YouTube has become the largest and most visited video-sharing platform, attracting users to educational content. Also, with over 500 million active users worldwide, TikTok has gained popularity in China with 150 million daily active users in China. The findings indicate how social media affects and transforms content creation and promotional strategies. So, this research provides a step forward to understanding digital promotion, which helps focus on the importance of social media technologies and social media platforms in contemporary video production. The practical use of the research is based on its findings for effective digital media promotion.
Keywords: visual storytelling, content promotion, platform algorithms, media technologies, media content, social media marketing